Direct Sums of Prime Subsemimodules (Jurnal Matematika, Statistika dan Komputasi, 2022)
Let  be a commutative semiring. A semimodule  over a semiring  is  a fully prime semimodule if each proper subsemimodule of  is prime. This research aims to investigate the relationship between a direct sum of prime subsemimodules   and  ,  , and a fully prime semimodule.
Keywords: prime subsemimodules; fully prime semimodules; semirings